Integrated Nanosensors to Determine Levels and Functional Activity of Human Telomerase - Perez, J Manuel (Neoplasia Press Inc., 2008)
Telomerase is a key oncogenic enzyme, and a number of novel telomerase inhibitors are currently under development. Because inhibition can be achieved either at the protein or at the enzymatic activity level, independent measurements of these parameters are important in the development of effective therapeutic agents. In the current study, we have developed a set of functional magnetic nanosensors capable of measuring the concentration of telomerase, as well as its enzymatic activity in parallel. The method is based on a magnetic relaxation switch assay, which can be performed in crude tissue samples and is fast and extremely sensitive. Using this method, we were able to detect different amounts of telomerase protein and activity in various cancer and normal cell lines. Furthermore, we were able to study the effect of phosphorylation on telomerase activity. This system not only could provide a rapid assay for the evaluation of antitelomerase therapies but could also be implemented to the study of other cancer markers.